Automated Determination of Grain Features for Wire Arc Additive Manufacturing - Karimi Javad; Bohlen Alan; Kamboj Neeraj; Seefeld Th (SPRINGER, 2025)
The morphology and size of the grains of the additively manufactured (AM) parts affect the mechanical properties and performance. The present research aimed to analyze the microstructure of AM parts, particularly the grain features, using image processing techniques. AMed aluminum components were fabricated using wire arc additive manufacturing based on cold metal transfer. The AA 5183 tensile samples fabricated using WAAM-CMT showed ductile behavior and the presence of the Luder bands. Metallographic sections were prepared, and fine equiaxed grain was observed. An automatic image evaluation program for determining the specified grain features was developed. The grain features, including size, area, perimeter, and sphericity, were quantified, and the obtained results were verified, indicating a satisfactory agreement with those obtained from manual measurement. The output of the image processing technique clearly proved that the MATLAB program, as an affordable and swift approach (similar to 4.8 s), can be used successfully to determine the microstructural properties. The image processing techniques could significantly improve the reliability and analysis of the microstructure, which would lead to the possibility of characterizing the microstructure in a broader range and having more details, and saving time and cost.